Business model adaptation for emerging markets: a case study of a German automobile manufacturer in India. (21st January 2016) - Landau, Christian; Karna, Amit; Sailer, Miriam
Abstract : Emerging markets offer a wide range of opportunities for firms from developed markets, especially in terms of high growth potential. However, business models that enable firms to achieve competitive advantage in their home markets are often challenged by the different nature of emerging markets. Firms, therefore, have to innovate and adapt their business models to better fit the specific context of these international markets. Based on a longitudinal case study of a German luxury automobile manufacturer's internationalization to India, we develop a phase model of the business model adaptation process to emerging markets. We find that firms adapt their business models in four phases: international extension, local emergence, local expansion, and local consolidation. Firms step‐wise adjust business model components along this process to develop a local emerging market business model. In each phase of the business model adaptation process, firms emphasize different components of the business model, before they enter into continuous adjustments of all business model components. Furthermore, we find that firms overall adjust some components of their business model more significantly than others. Our findings are of particular relevance to the literature on business model internationalization and the literature that points out the evolutionary, step‐wise nature of business model innovation.